Challenges to sustainable Arctic tourist lodging: a proposed solution for Greenland. (September 2015) - Qu, Jing; Villumsen, Arne; Villumsen, Ole
ABSTRACT The beauty of nature in Greenland and the selling point of Greenlandic tourism 'Our ice is melting, yet it is still here' have been attracting more tourists in recent years. Therefore, demand for tourist accommodation is expected to grow in the future. Staying overnight in small huts is a traditional way for nomadic Greenlanders and for tourists. However, the austere condition of the existing huts cannot meet requirements nowadays. Meanwhile, climate change is causing retreat of ice, so tourist attractions might change in the future. Therefore the contradiction of 'improved lodging', 'environmental friendliness' and 'flexibility of location' raise the problem for the future development of tourist accommodation. The aim of this work is to explore a desirable solution by developing stand-alone mobile tourist huts with light and heating based on renewable energy supply, and sustainable black waste water management. The cabin can be disassembled into pieces and transported to new areas by trucks, snow scooters, boats or dog-sledges with almost no disturbance to the environment of the original location. In addition, cultural sustainability is also taken into account.